Perturbations in gut microbiota composition in patients with autoimmune neurological diseases: a systematic review and meta-analysis - Deng, Xiaolin; Gong, Xue; Zhou, Dong; Hong, Zhen (Frontiers in Immunology, 2025)
Studies suggest that gut dysbiosis occurs in autoimmune neurological diseases, but a comprehensive synthesis of the evidence is lacking. Our aim was to systematically review and meta-analyze the correlation between the gut microbiota and autoimmune neurological disorders to inform clinical diagnosis and therapeutic intervention. We searched the databases of PubMed, Embase, Web of Science, and the Cochrane Library until 1 March 2024 for research on the correlation between gut microbiota and autoimmune neurological disorders. A total of 62 studies provided data and were included in the analysis (n = 3,126 patients, n = 2,843 healthy individuals). Among the included studies, 42 studies provided data on α-diversity. Regarding α-diversity, except for Chao1, which showed a consistent small decrease (SMD = −0.26, 95% CI = −0.45 to −0.07, p < 0.01), other indices demonstrated no significant changes. While most studies reported significant differences in β-diversity, consistent differences were only observed in neuromyelitis optica spectrum disorders. A decrease in short-chain fatty acid (SCFA)-producing bacteria, including Faecalibacterium and Roseburia, was observed in individuals with autoimmune encephalitis, neuromyelitis optica spectrum disorders, myasthenia gravis, and multiple sclerosis. Conversely, an increase in pathogenic or opportunistic pathogens, including Streptococcus and Escherichia-Shigella, was observed in these patients. Subgroup analyses assessed the confounding effects of geography and immunotherapy use. These findings suggest that disturbances of the gut flora are associated with autoimmune neurological diseases, primarily manifesting as non-specific and shared microbial alterations, including a reduction in SCFA-producing bacteria and an increase in pathogenic or opportunistic pathogens.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023410215.